THE IMPLANT TREATMENT OF TWO PATIENTS SUFFERING FROM SJÖGREN’S SYNDROME WITH MULTIFACTORIAL REGENERATIVE PROTOCOL - Corigliano, M.; Re, M.; Cipollina, A.; Crescentini, F.; Docaj, D.; Baldoni, E. (European Scientific Journal, ESJ, 2014)
The purpose of the work is to show that it is possible to rehabilitate with Multifatorial Regenerative Protocol (MFRP) also the patients with diseases considered to be absolute contraindications to the implant rehabilitation. For the rehabilitation it has been used the PBR rehabilitation technique, that allows to insert prosthetic roots not excessively traumatizing the bone tissue and to avoid the use of high speed rotary burs. Despite the disease and the poor bone quality, it has been possible to obtain the osteo-connection only in 45 days. Using the MFRP implants, it is possible to rehabilitate with a high percentage of success also patients with poor bone quality and density.